Forces and Trauma Associated with Minimally‐Invasive, Image‐Guided Cochlear Implantation. (23rd August 2013) - Rohani, Pooyan; Pile, Jason; Kahrs, Lueder; Balachandran, Ramya; Blachon, Gregoire; Simaan, Nabil; Labadie, Robert F.
Abstract : Objectives: Minimally‐invasive, image‐guided cochlear implantation (CI) uses a patient‐customized microstereotactic frame to access the cochlea via a single drill‐pass. We investigated the average force and trauma associated with the insertion of lateral wall CI electrodes using this technique. Methods: Microstereotactic frames for 6 fresh cadaveric temporal bones were built using computed tomography (CT) scans to determine an optimal drill path, following which drilling was performed. A tympanomeatal flap was raised, the round window (RW) overhang was taken down, and the RW membrane was reflected posteriorly. CI electrodes were inserted using surgical forceps to manually advance the CI electrode array, via the drilled tunnel, into the cochlea. Forces were recorded using a 6‐axis load sensor placed under the temporal bone during insertion of lateral wall electrode arrays (2 each of Nucleus CI422, MED‐EL standard, and MED‐EL standard with stiffeners). Tissue histology was performed by removing the lateral wall of the cochlea allowing photo‐documentation of electrode position and microscopic assessment of intracochlear tissue. Results: After drilling, CT scanning demonstrated successful access to cochleae in all 6 bones. Average insertion forces were 0.0088‐0.0780N. Peak forces were 0.0564‐0.4688N. Single factor analysis of variance was not statistically significant comparing average forces of different electrodes ( P = 0.77). Tissue histology showed complete scala tympani insertion in all specimens with depth of insertion ranging from 360‐600°. No intracochlear trauma was identified. Conclusions: In this cadaver model with a minimally‐invasive, image‐guided CI approach, the use of lateral wall electrodes was associated with insertion forces comparable to traditional CI surgery. Deep insertions were obtained without identifiable trauma.